Tetraploid cells produced by absence of substrate adhesion during cytokinesis are limited in their proliferation and enter senescence after DNA replication. Issue 2 (17th January 2016) - De Santis Puzzonia, Marco; Gonzalez, Laetitia; Ascenzi, Sonia; Cundari, Enrico; Degrassi, Francesca
ABSTRACT: Tetraploidy has been proposed as an intermediate state in neoplastic transformation due to the intrinsic chromosome instability of tetraploid cells. Despite the identification of p53 as a major factor in growth arrest of tetraploid cells, it is still unclear whether the p53-dependent mechanism for proliferation restriction is intrinsic to the tetraploid status or dependent on the origin of tetraploidy. Substrate adherence is fundamental for cytokinesis completion in adherent untransformed cells. Here we show that untransformed fibroblast cells undergoing mitosis in suspension produce binucleated tetraploid cells due to defective cleavage furrow constriction that leads to incomplete cell abscission. Binucleated cells obtained after loss of substrate adhesion maintain an inactive p53 status and are able to progress into G1 and S phase. However, binucleated cells arrest in G2, accumulate p53 and are not able to enter mitosis as no tetraploid metaphases were recorded after one cell cycle time. In contrast, tetraploid metaphases were found following pharmacological inhibition of Chk1 kinase, suggesting the involvement of the ATR/Chk1 pathway in the G2 arrest of binucleated cells. Interestingly, after persistence in the G2 phase of the cell cycle, a large fraction of binucleated cells become senescent. These findings identify a new pathway of proliferation restriction for tetraploid untransformed cells that seems to be specific for loss of adhesion-dependent cytokinesis failure. This involves Chk1 and p53 activation during G2. Inhibition of growth and entrance into senescence after cytokinesis in suspension may represent an important mechanism to control tumor growth. In fact, anchorage independent growth is a hallmark of cancer and it has been demonstrated that binucleated transformed cells can enter a cycle of anchorage independent growth.